tRNA-Derived Fragment tRF-Glu-TTC-027 Regulates the Progression of Gastric Carcinoma via MAPK Signaling Pathway - Xu, Weiguo; Zhou, Bin; Wang, Juan; Tang, Li; Hu, Qing; Wang, Jian; Chen, Huanhuan; Zheng, Junyu; Yan, Feng; Chen, Huanqiu (Frontiers in Oncology, 2021)
Transfer RNA-derived RNA fragments (tRFs) belong to non-coding RNAs (ncRNAs) discovered in most carcinomas. Although some articles have demonstrated the characteristics of tRFs in gastric carcinoma (GC), the underlying mechanisms still need to be elucidated. Meanwhile, it was reported that the MAPK pathway was momentous in GC progression. Thus we focused on investigating whether tRF-Glu-TTC-027 could act as a key role in the progression of GC with the regulation of the MAPK pathway. We collected the data of the tRNA-derived fragments expression profile from six paired clinical GC tissues and corresponding adjacent normal samples in this study. Then we screened tRF-Glu-TTC-027 for analysis by using RT-PCR. We transfected GC cell lines with tRF-Glu-TTC-027 mimics or mimics control. Then the proliferation, migration, and invasion assays were performed to assess the influence of tRF-Glu-TTC-027 on GC cell lines. Fluorescence in situ hybridization assay was conducted to confirm the cell distribution of tRF-Glu-TTC-027. We confirmed the mechanism that tRF-Glu-TTC-027 influenced the MAPK signaling pathway and observed a strong downregulation of tRF-Glu-TTC-027 in clinical GC samples. Overexpression of tRF-Glu-TTC-027 suppressed the malignant activities of GC in vitro and in vivo. MAPK signaling pathway was confirmed to be a target pathway of tRF-Glu-TTC-027 in GC by western blot. This is the first study to show that tRF-Glu-TTC-027 was a new tumor-suppressor and could be a potential object for molecular targeted therapy in GC.